2023
DOI: 10.1152/ajplung.00296.2022
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acids improve inflamm-aging and acute lung injury in old mice

Abstract: A chronic pro-inflammatory milieu (inflamm-aging) is observed in the elderly and associated with poorer prognosis in acute lung injury (ALI). Gut microbiome-derived short chain fatty acids (SCFAs) are known to have immunomodulatory capabilities, but their function in the gut-lung axis in aging is poorly understood. Here we analyzed the gut microbiome and its impact on inflammatory signaling in the aging lung and tested the effects of SCFAs in young (3 months) and old (18 months) mice that received either drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…SCFAs also play an important role in the immune response of the host and in metabolism. Numerous studies have shown that the gut microbiota can modulate SCFAs to alleviate acute lung injury [ 54 , 55 , 56 ]. In the present study, heat-inactivated MRSA induced a decrease in SCFAs in ALI in mice, and propolis pretreatment elevated the concentrations of acetic acid and valeric acid to reverse these changes.…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs also play an important role in the immune response of the host and in metabolism. Numerous studies have shown that the gut microbiota can modulate SCFAs to alleviate acute lung injury [ 54 , 55 , 56 ]. In the present study, heat-inactivated MRSA induced a decrease in SCFAs in ALI in mice, and propolis pretreatment elevated the concentrations of acetic acid and valeric acid to reverse these changes.…”
Section: Discussionmentioning
confidence: 99%
“…When short-chain fatty acids are supplemented, inflammation and oxidative stress are reduced in the lungs of aging mice, as well as the increased inflammatory signal in acute lung injury in these mice. 60 A fatty acid derivative of quercetin-3-O-glucoside prevents cigarette smoke extract-induced cell death and membrane lipid peroxidation in human fetal lung fibroblasts. 61 As a result of these studies, lipids and their derivatives have been implicated as a critical pathogenic factor in COPD and other lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism connecting dietary fiber and risk of COPD is unknown, the positive benefits from greater dietary fiber intake in the general population have been postulated to be related to improved gut microbiome and reduced inflammatory responses [ 64 ]. Fiber fermentation results in the formation of metabolites such as short-chain fatty acids [ 65 ], which are known to have systemic [ 66 ] and pulmonary anti-inflammatory effects [ 67 ]. Diets low in fiber can also result in gut dysbiosis and promote chronic, systemic inflammation [ 68 ].…”
Section: Dietary Fibermentioning
confidence: 99%